Pengaruh Pendapatan, Literasi Keuangan, dan Pengetahuan Investasi terhadap Minat Investasi Syariah di Kecamatan Kartasura Sukoharjo - Annisa Marshanda Rahmawati; Prastiwi, Iin Emy; Agus Marimin (ITB AAS INDONESIA Surakarta, 2025)
This research aims to determine the influence of income, financial literacy, and investment knowledge on interest in sharia investment in Kartasura District. This research is quantitative research that uses primary data with data collection techniques using questionnaires distributed randomly to 100 respondents. This research uses a descriptive statistical data analysis method with the help of IBM SPSS Statistics version 23 software and hypothesis testing is carried out using a partial test (t test) with a significance level of 5%. The results obtained from the partial test (t test) are that income has no significant effect on interest in sharia investment in Kartasura District. Meanwhile, financial literacy and investment knowledge have a partially significant effect on interest in sharia investment in Kartasura District.